The Patho-Histological Change of Fetus Amniotic Sac as a Result of Bacterial Infection - Sura I. A. Jabuk (Journal of Global Pharma Technology, 2017)
Amniotic fluid is defined as a transparent liquid that is present in the uterus during pregnancy. In this study obtain 100 sample of vaginal swaps(50from normal birth and 50 from caesarean), 100 samples of amniotic fluid (50 samples from normal birth and 50 samples from caesarean) from pregnant women revision born lounge  in Hilla teaching hospital, and 50 samples of amniotic sac from the caesarean women to made histological section. The result showed the number of positive swaps of bacteria  was 81 (81%) , while positive samples from amniotic fluid was 76 (74%) from the total 100 sample and present relationships between vaginal  infection and the present of bacteria in the amniotic fluid .The  type of  aerobic bacteria isolated was Escherichia coli ,Pseudomonas aeruginosa, Bacillus subtilis, Klebsiella pneumonia, Staphylococcus epider midis, Staphylococcus aureus,  Streptococcus  mutans, Proteus mirabilis and anaerobic bacteria was Peptp streptococcus sp. Neisseria gonorrhoeae, Lactobacillus sp. and Actinomyces sp. were isolated from amniotic fluids and vaginal swabs. then injection the same bacteria isolated in mice and made histological section from mice amniotic sac. Cross section of amniotic tissues in both of women and mice showed infiltration of lymphocyte, hemorrhage and elongation of epithelial cell as a result of bacterial infection.Keywords: Amniotic fluid, Amniotic sac, Caesarean, Vaginal infection. In vitro, In vivo.